Socio-demographic factors influencing practice and awareness of exclusive breastfeeding benefits among women of reproductive age attending maternal and child health clinic in Tudor Sub-County Hospital - Machila, Consolata Mandi; Karonjo, Jane; Mogere, Dominic; Kariuki, Peterson (International Journal of Community Medicine and Public Health (Medip Academy), 2021)
Background: Knowledge of exclusive breastfeeding (EBF) among women is essential for promoting optimal infant nutrition. Breastfeeding is recommended exclusively for the first six months of life, followed by complementary feeding up to two years or beyond. Methods: A descriptive cross-sectional study was conducted among 422 mothers attending the Tudor Sub-County MCH clinic in Mombasa, Kenya. Both qualitative and quantitative methods were applied. Results: Four socio-demographic factors significantly influenced EBF practice: child gender, maternal education, marital status, and parity. Awareness of the benefits of EBF was influenced by maternal education and occupation. Conclusion: Efforts to improve women’s education and create supportive workplace conditions are essential to increase exclusive breastfeeding rates.
Exclusive breastfeeding awareness and practice among women in Tudor Sub-County, Kenya
This article contributes evidence on the socio-demographic determinants of exclusive breastfeeding in Kenya, with implications for child survival, maternal health, and health system interventions aligned with SDG 2 and SDG 3.
Keywords: Exclusive breastfeeding; Maternal and child health; Socio-demographic factors; Nutrition practices; Kenya